Kajian Potensi Penggunaan Bioreaktor terhadap Senyawa Ajmalisin Suatu Contoh Produksi Metabolit Sekunder Tanaman Obat - Saraswati, Ratih Dian (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2012)
The limited availability of medicinal plants as well as their limitations in cultivation as a source of medicinal compounds can lead to excessive harvesting, habitat destruction and destructive exploration. This led to the extinction of rare plants and caused the condition of natural resources worse. The purpose of this study is to elucidate the potential of bioreactor in terms of its ability to increase the active compounds of plant obtained from C. roseus ajmalicine. The data was obtained from various references. The main references discuss about ajmalicine and bioreactor.In general, the concentration of compounds produced by cell suspension is higher than its original concentration in the plants. In study cases of ajmalicine, the compounds were produced as much as seven times more than these compounds in native plants. Other studies show that the use of different plant organs, the addition of elicitor, the weight ofinitial cells as well as aeration rate can affect the concentration of ajmalicine obtained from medium in the bioreactor. Tissue cultured plants in bioreactor can produce secondary metabolites in a short time with high yields. However, previous optimazation should be carried out in terms of adding elicitor, aeration rate and pH condition of the bioreactor